2009
DOI: 10.1038/hr.2009.55
|View full text |Cite
|
Sign up to set email alerts
|

Role of renin–angiotensin system in adipose tissue dysfunction

Abstract: Blockade of angiotensin II type 1 (AT 1 ) receptor improves insulin sensitivity and diabetic condition. In short-term regulation, angiotensin II changes lipid metabolism and in long-term regulation, it affects insulin sensitivity and adipocyte differentiation in adipose tissue. These effects are mainly mediated by AT 1 receptor. AT 1 receptor blocker improves insulin sensitivity and induces adipocyte differentiation by increasing peroxisome proliferator-activated receptor-c (PPARc) and transcription factors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Animal studies have shown that ACE inhibitors enhance cognitive performance (48), and improve learning and retention of memory (49). On the other hand, overstimulation of AT1R leads to cognitive deficits and ischemic damage in mice (32,33), as well as hypertension, vascular brain damage, and insulin resistance in humans (50). Thus, it is tempting to suggest that a hypercholesterolemia-mediated overactivation of brain RAS, via the BBB permeable 27-OH, may contribute to neurodegenerative processes including memory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that ACE inhibitors enhance cognitive performance (48), and improve learning and retention of memory (49). On the other hand, overstimulation of AT1R leads to cognitive deficits and ischemic damage in mice (32,33), as well as hypertension, vascular brain damage, and insulin resistance in humans (50). Thus, it is tempting to suggest that a hypercholesterolemia-mediated overactivation of brain RAS, via the BBB permeable 27-OH, may contribute to neurodegenerative processes including memory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…These include cellular growth (hypertrophy) and remodelling (fibrosis); dyslipidaemia; endothelial dysfunction, aneurysms and angiogenesis (Iwai and Horiuchi, 2009;Lu et al, 2008;Mehta and Griendling, 2007;Weiss et al, 2001); proinflammatory responses (Rompe et al, 2010;Schiffrin, 2010); stem cell programming and haematopoiesis (Heringer-Walther et al, 2009;Park and Zambidis, 2009;Zambidis et al, 2008); neuromodulation including cognition, memory and dementia (Li et al, 2010;Miners et al, 2009); and cancer, as reviewed by us (George et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, it is suggested that angiotensin receptor blocker could increase insulin secretion at animals with type-II diabetes. Additionally, it is reported to enhance glucose uptake at adipose tissue, one of the sensitive insulin organs, at AT2-knockdown animals [44]. Alternative RAS pathways, ACE2/An-1-7/Mas axis, might be the high beneficial effect on diabetes based on enhancing glucose reuptake, diminishing glycogen production, and insulin resistance in hepatocytes via Akt/PI3K/IRS-1/JNK insulin signaling.…”
Section: The Local Renin-angiotensin System In Liver and Insulin Resimentioning
confidence: 99%